Introduction to the Islamic Worldview: Study of Selected Essentials - Abdelaziz Berghout ed (IIUM Press, 2010)
This book sheds some light on the Islamic Worldview and its vital role in the renewal of the Muslim Ummah. In principle, the Islamic worldview stands as the cementing force behind the making of the Islamic civilization and its progress in history and society. The book deals with the Islamic worldview not only from a theological perspective, but more importantly from a comprehensive perspective stressing its civilizational implications in the life of the Muslim and the Ummah as well. On the other hand, this book provides important information on the various aspects of the Islamic worldview as well as the western worldview so as to assist the reader to grasp and appreciate the distinctive features of Islam and its vision of life. This book creatively summarizes many scattered ideas and ties together many important aspects of the Islamic worldview reflecting its coherent and consistent vision of life. Additionally, it highlights the essential role of the concept of TawÃÃŠd in human existence and life. Last but not least, this book adds another vital brick into the works and studies related to the Islamic worldview, opening a new horizon on this field of study.